ISOLASI DAN IDENTIFIKASI SENYAWA TERPENA HASIL PIROLISIS GETAH KARET ALAM (Hevea brasiliensis) - , JOHANIS WAIRATA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Isolation and identification of terpenes obtained from the pyrolisis of natural rubber (Hevea brasiliensis) latex have been conducted. The latex was pyrolized under reduced pressure without any solvent. The pyrolysis products included water, protein and rubber oil. The rubber oil was separated and identified using GC-MS. The results showed that the rubber oil contained 22 compounds. According to literature review, 12 compounds were identified as terpene, including monoterpene, sesquiterpene and diterpene. Monoterpene compounds were isolimonene, l-limonene, Î²-felandrene, d-limonene and camphene. The identified sesquitterpenes were 2,4a,8,8-tetramethyl-1,1a,4,4a,5,6,7,8-octahydrocyclopropane [d] naphthalene, Î²-farnasene, Î±-amorphene, Î³-amorphene and bisabolene. The analyzed diterpenes were abietadiene and kaurene. The dominant terpene was d-limonene. The dlimonene was isolated using fractional distillation and had the purity of 96.79%.